Experimental investigation of sandwich panel subjected to transverse point load - Mohamad Taufik. (2009)
Low velocity impact tests were conducted on carbon fibre reinforced epoxy sandwich panels of 10 ply laminate with configuration of [+45/-45/0/90/0]s in order to investigate the load bearing capabilities and energy absorption characteristics of the sandwich panels and identify quantifiable trends.